Sustainable Industrialization in Africa Towards a New Development Agenda - Oyelaran-Oyeyinka, Banji; Gehl Sampath, Padmashree (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Sustainable Industrialization in Africa explores the issues that confront development policy in the context of the MDGs and the post-2015 development agenda from an African perspective. The book argues that development is an ultimate outcome of sustainable, equitable industrialization, and that any development agenda for the future has to ensure that industrialization is fostered in a way that makes economies independent and responsive to the needs of all citizens. Future challenges for sustainable industrialization in Africa, based upon the differences in its current industrialization trajectories, are discussed to ensure that industrial growth results in positive economic and social outcomes in the context of the post-2015 development agenda.